Hydroxyapatite mixed-electro discharge formation of bioceramic Lakargiite (CaZrO3) on Zr–Cu–Ni–Ti–Be for orthopedic application. Issue 16 (10th December 2018) - Aliyu, Abdul Azeez Abdu; Abdul-Rani, Ahmad Majdi; Ginta, Turnad Lenggo; Rao, T. V. V. L. N.; Selvamurugan, Nagarajan; Roy, Sandipan
ABSTRACT: To suit a target application, the machining mechanism of electro discharge machining (EDM) process has been hybridized to powder mixed EDM (PM-EDM) by adding various substances in the form of additives into the dielectric fluid. In this study, the application of PM-EDM to fabricate Lakargiite (CaZrO3 ) coating on Zr–Cu–Ni–Ti–Be substrate surface for potential orthopedic application, using hydroxyapatite (HA) powder as dielectric additive was proposed. The effect of various HA powder concentrations on deposition of CaZrO3 on Zr–Cu–Ni–Ti–Be surface was investigated. Zr–Cu–Ni–Ti–Be bulk metallic glass (BMG) has exceptional mechanical and chemical properties compared to its crystalline counterpart. It is expected that, the formation of a nanoporous bioactive CaZrO3 coating on the BMG surface will enhance its bioactivity. The FESEM investigation presents the formation of various interconnected shallow craters, nanopores, and few nanocracks and the energy dispersive X-ray spectroscopy results depict the presence of about 50% Lakargiite phase on the HA-deposited BMG surface. The X-ray powder diffraction characterization identified the phases includes ZrC, ZrO, TiC, and CaTiO3 formed on the PM-EDMed surface. The Rockwell hardness testing revealed the rise of BMG surface hardness to about 42%. The roughness of EDMed surface reduced from 6.22 nm to 2.00 nm after HA powder suspended in the dielectric fluid.